Bibliometric Analysis: The Impact of Anxiety on Patiens With Chronic Kidney Disease With The Logo of Therapy and Cognitive Behavior Therapy in Indonesia - mugihartadi, Mugihartadi; Said, Faridah Mohd; Nambiar, Nisha; Pramesthi, Bernadine Avelia Riana (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
The study conducted a bibliometric analysis of the impact of anxieties on patients with chronic kidney disease in an effort to lessen patient anxiety. This bibliometric analysis looks at research activities in Indonesia and globally using publication data from the Scopus database. In bibliometric analysis, quantitative techniques are employed to assess data and generate representative images. It is acknowledged that this study is a valuable tool for assessing research topic characteristics, publication outputs, and composition and structure. Between 1955 and 2023, attempts to lower anxiety through cognitive behavioral and logotherapy were successful, despite a lack of significant overall growth.